Manajemen Pengolahan Bank Sampah Untuk Meningkatkan Kesadaran Manfaat Sampah Di Desa Tamansari Kecamatan Wonorejo Kabupaten Pasuruan - Mochamad Mas’ud (LPPM Universitas Yudharta Pasuruan, 2021)
Garbage is a problem that is often faced in almost every country. More and more waste will certainly cause many problems, so it requires processing such as making waste into useful and economical materials. Not only in developing countries, waste is also the biggest problem in Indonesia, one of which is in Tamansari village, Wonorejo sub-district, Pasuruan district. In the village, the community is very less understanding in terms of managing waste. With this problem in Tamansari village, community sevice program helps to overcome the waste problem so that it is controlled and does not pollute the local environment. In this study, our group community sevice program invited village heads, waste banks, and residents to continue the existing waste bank program to be more optimal. We use the observation method regarding the conditions and problems being faced, socialization about proper waste management for these residents and educating the public about the importance of waste banks for the economy and cleanliness of the surrounding environment. In addition to this method, our group also conducted direct interviews with one of the residents who had their own yard, to be asked not to throw garbage in the yard to make it easier and more effective. Monitoring and Evaluation Every work program that we have planned can be carried out properly and according to a predetermined schedule but from the implementation there can still be shortcomings that must be addressed, considering that the village community lacks knowledge about technology, especially this application. In addition to the time constraints, conditions that are currently in this pandemic period, we are not very satisfied in carrying out this program. In this community sevice program, the focus is more on waste bank management, because in the village there is already a waste bank but it is still not implemented properly, therefore our group tends to develop this program rather than the waste digitization program.